Bioecology and Distribution of Dwarf Snakehead (Channa limbata, Cuvier 1831) Based on Geographic Information System in Progo River, Magelang, Central Java - Tholibah Mujtahidah; Sri Hidayati; Abdul Qadir Jailani; Annisa Novita Sari; Muhammad Tri Aji; Eric Armando (Journal of Aquaculture and Fish Health, 2023)
This research was a database collection process to determine the resources of dwarf snakehead C. limbata and found the potential fish resources in the Progo river forming of a zonation map, so it was very necessary to determine the next step in the management of fish resources (domestication efforts) of potential commodities in Magelang. The research was conducted from May to November 2021. Parameters observed were morphometric, length-weight relationship, gonad maturity level, feed, condition factor, and water quality. The tools used in this research were GPS for determining sampling points, nets for catching fish, etc. The results showed that dwarf snakehead was a demersal fish that lived in freshwater with an environmental condition with muddy sand and rocky gravel as its natural habitat. The morphology was rounded tail shape, protocercal tail type and ctenoid scales. The growth pattern was allometric negative. Gonad maturity stage of male (GMS 1) and female (second development / GMS 4). The GSI value for males was 0.0875 and females was 0.729. The GI value for males was 0.06 and females was 0.551. Plankton found in the stomach include Leptocylindrus sp., Cylindrospermopsis sp., Rotaria neptunia, Dipleuchlanis propatula and Conochilus hippocrepis.